Perceived Vulnerability to Downside Risk - Felix Povel (Georg-August-Universität Göttingen, Courant Research Centre - Poverty, Equity and Growth (CRC-PEG), 2010)
In this paper we propose an approach to vulnerability called perceived vulnerability to downside risk. We argue that the other concepts of vulnerability, though partially adhering to the focus axiom, do not exclusively consider downside risks in their measures. The reason for this is that most of them use a pre-determined threshold such as the poverty line as their benchmark for analysis. Instead, we opt for the current level of wellbeing of a household as reference point. Also, we propose to use subjective risk perception as the source of information for quantifying vulnerability since it overcomes some of the shortcomings connected to the reliance on information about the past. Finally, we apply the measure of perceived vulnerability to downside risk to risk perception data from Thailand and Vietnam and find that households in the latter country tend to be more vulnerable than households in the former. Moreover, determinants of perceived vulnerability to downside risk differ significantly between the two countries.
Keywords: D81; I31; I32; O12; 330; Vulnerability; Risk; Risk Perception; Subjective Wellbeing